Sensing R-Loop-Associated DNA Damage to Safeguard Genome Stability - Rinaldi, Carlo; Pizzul, Paolo; Longhese, Maria Pia; Bonetti, Diego (Frontiers in Cell and Developmental Biology, 2021)
DNA transcription and replication are two essential physiological processes that can turn into a threat for genome integrity when they compete for the same DNA substrate. During transcription, the nascent RNA strongly binds the template DNA strand, leading to the formation of a peculiar RNA–DNA hybrid structure that displaces the non-template single-stranded DNA. This three-stranded nucleic acid transition is called R-loop. Although a programed formation of R-loops plays important physiological functions, these structures can turn into sources of DNA damage and genome instability when their homeostasis is altered. Indeed, both R-loop level and distribution in the genome are tightly controlled, and the list of factors involved in these regulatory mechanisms is continuously growing. Over the last years, our knowledge of R-loop homeostasis regulation (formation, stabilization, and resolution) has definitely increased. However, how R-loops affect genome stability and how the cellular response to their unscheduled formation is orchestrated are still not fully understood. In this review, we will report and discuss recent findings about these questions and we will focus on the role of ATM- and Rad3-related (ATR) and Ataxia–telangiectasia-mutated (ATM) kinases in the activation of an R-loop-dependent DNA damage response.